Melatonin prevents gestational hyperhomocysteinemia-associated alterations in neurobehavioral developments in rats - Baydas, Giyasettin; Koz, Sema T.; Tuzcu, Mehmet; Nedzvetsky, Viktor S. (Wiley, 2008)
Chronic hyperhomocysteinemia is a risk factor in cardiovascular diseases and neurodegeneration. Among the putative mechanisms of homocysteine-induced neurotoxicity, an increased production of reactive oxygen species has been suggested. However, elevated homocysteine levels might disturb neurogenesis during brain development and lead to persistent congenital malformations in the fetus. In this study, we examined whether administration of melatonin inhibits maternal hyperhomocysteinemia-induced cognitive deficits in offspring. Hyperhomocysteinemia was induced in female rats by administration of methionine during pregnancy at a dose of 1 g/kg body weight dissolved in drinking water. Some animals received methionine plus 10 mg/kg/day melatonin subcutaneously throughout pregnancy. The levels of glial fibrillary acidic protein, S100B protein, and neural cell adhesion molecules were determined in the brain tissue from the pups. Learning and memory performances of the young-adult offspring were tested using the Morris water maze test. There were significant reductions in the expression of glial fibrillary acidic protein and S100 B protein in the brains of pups from hyperhomocysteinemic rat dams. Furthermore, maternal hyperhomocysteinemia altered the expression pattern of neural cell adhesion molecules in the fetal brain. In addition, maternal hyperhomocysteinemia significantly reduced learning abilities in offspring. Treatment with melatonin during pregnancy improved learning deficits and prevented the reduction of glial and neuronal markers induced by hyperhomocysteinemia. In conclusion, administration of melatonin throughout pregnancy reduces the effects of hyperhomocysteinemia on the development of fetal brain; therefore, it might be beneficial in preventing persistent congenital malformations.
Keywords: fetus; hyperhomocysteinemia; learning; melatonin; neurodevelopment